BOLAJAQ OQÍTÍWSHÍLARDÍŃ KÁSIPLIK TAYARLÍǴÍN WEB-TEXNOLOGIYALAR TIYKARÍNDA JETILISTIRIWDIŃ DIDAKTIKALÍQ MÚMKINSHILIKLERI - Mambetniyazov, M.T.; Auezova, R.K. (ILIM hám JÁMIYET, 2024)
The didactic possibilities of providing professional training of future teachers on the basis of Web-technologies, the work and problems that need to be worked on in this direction are expressed in the article.